A Study on the Dynamic Evolution and Prevention of Technological Innovation Risks in Major Railway Projects - Feng Guo; Qixuan Liu; Lemin Li; Yixue Zuo; Yifang Pan; Wanping Pan (Buildings)
Technological innovation risk in major railway projects is high, and the risk factors in the innovation process are complex and variable. In order to successfully complete the goal of technological innovation in major railway projects. This paper identifies the risk factors of technological innovation in major railway projects, establishes a system dynamics model of technological innovation risk evolution, and carries out simulation analysis by taking the C railway project as an example, to understand the risk evolution process, clarify the key tasks of risk prevention, and finally draw the following research conclusions: (1) Technological innovation risk is categorized into innovation management risk, technology R&D risk, and technology application risk, of which innovation management risk has a greater impact on technological innovation risk. (2) During the construction process, the risk of technological innovation shows a general trend of increasing and then stabilizing, with the technology R&D stage being the centralized emergence stage of technological innovation risk. (3) Changes in the values of risk factors will have different degrees of impact on technological innovation risk, with changes in planning and implementation having the greatest impact on the technological innovation risk system, followed by the feasibility of results, and changes in the value of technological difficulties risk having a lesser impact on the system. The results of this study can provide lessons and references for the prevention of technological innovation risks in major railway projects.